Long‐term data reveal contrasting impacts of native versus invasive nest predators in Iceland - Jón Einar Jónsson; Fiona S. Rickowski; Florian Ruland; Árni Ásgeirsson; Jonathan M. Jeschke (Ecology Letters, 2023)
Bird species on islands are strongly impacted by biological invasions, with the Icelandic common eider ( Somateria mollissima borealis ) being particularly threatened. Down collection by local families in Breiðafjörður, West Iceland, provided long‐term datasets of nests from two archipelagos, covering 95 islands over 123 years and 39 islands over 27 years, respectively. Using these exceptional datasets, we found that the arrival of the invasive semi‐aquatic American mink ( Neogale vison ) was a more impactful driver of population dynamics than climate. This invasive predator heavily reduced eider nest numbers by ca. 60% in the Brokey archipelago. In contrast, we detected an apparently adaptive response to the return of the native fox in the Purkey archipelago, with dense nests on islands inaccessible to the fox and no apparent impact on eider populations. This difference might be due to the eiders lacking a joint evolutionary history with the mink and therefore lacking appropriate antipredator responses.